Distribution of SCCmec-associated phenol-soluble modulin in staphylococci - SHORE, ANNA; COLEMAN, DAVID (My University, 2012)
The recently described phenol-soluble modulin PSM-mec was detected in S. aureus, S. epidermidis, S. fleuretti, S. hominis, S. pseudintermedius, S. saprophyticus, S. simulans and S. vitulinus from different hosts (humans, goats, dogs, cats, pigs, cattle and turkeys). It was identified in isolates harbouring SCCmec types II, IIA, IIB, IID, III, VIII and in some irregular or truncated elements.
PUBLISHED
Keywords: Genomics; Infection; Staphylococcus